Deficiency of a peroxisomal NADP-isocitrate dehydrogenase leads to dwarf plant and defect seed in upland cotton - Cao, Yuefen; Wang, Wanru; Chen, Jinhong; Zhu, Shuijin; Zhao, Tianlun (Frontiers in Plant Science, 2022)
The NADP-isocitrate dehydrogenase encoded gene GH_D13G1452 with a C-terminus tripeptide Proline-Lysine-LeTcine was localized in peroxisome. It expressed highly in stem and ovules of 15 days post-anthesis, and responded to multiple external stimuli in upland cotton. A upland cotton mutant (Ghpericdh) was identified from flanking sequence amplification and genome variation detection that exogenous sequence was inserted in the middle of the 12th intron of GH_D13G1452, resulting in the deficiency of gene expression. The Ghpericdh mutant displayed dwarf plant phenotype when grown in either a field or a greenhouse, and GH_D13G1452 functioned as an incomplete dominance on plant height. The germination rate of mutant seed from greenhouse-grown plants was dramatically lower than that from field-grown plants, which indicated that GhperICDH plays a critical role in seed maturation and germination. Therefore, GH_D13G1452 is indispensable in the development of stem and seed, and functions in the adaptability of cotton to the environment. The Ghpericdh mutant provides insight into the function of peroxisomal ICDH and may contribute to the genetic improvement in cotton.